Quality of work-life and work performance in physicians at the Mexican Institute of Social Security, in the state of Chiapas - López-Martínez, Brenda Esther (2021)
Introduction: Maintaining a quality of working life brings as a benefit a greater productivity. Objective: To know if the quality of work life is a significant predictor of the level of self-perceived work performance by the doctors who work at the Mexican Institute of Social Security of Well-being, in the state of Chiapas. Material and methods: The study had a quantitative, cross-sectional and predictive approach. The population consisted of 445 doctors. The type of sampling was non-probabilistic for convenience, since the doctors who work in the Mexican Institute of Social Security (IMMSS) Bienestar, in the state of Chiapas, were selected. The sample consisted of 169 physicians who represent 37.97% of the population. A simple linear regression analysis was carried out by the method of successive steps. Results: It was found that the variable level of working life described 64.9% of the variance of the dependent variable level of job performance. Similarly, it was determined that there is a positive and significant linear influence between the variables. The quality of work life variable was found to be a significant predictor of work performance in a very important way (β = .806). Conclusions: It was found that the quality of work life influences the work performance of the doctors who work in the Mexican Institute of Social Security of Well-being, in the state of Chiapas in a very important way. To the extent that the surveyed doctors improve their quality of work life, it will influence their work performance.